НАУКОМЕТРИЧНІ ПОКАЗНИКИ ЖУРНАЛУ "ТЕХНІЧНА ЕЛЕКТРОДИНАМІКА" У МІЖНАРОДНІЙ БАЗІ ДАНИХ SCOPUS 2016 р. - Городжа, Л.В. (Інститут електродинаміки НАН України, Київ, 2017)
The main scientometric indicators of the journal "Technical Electrodynamics" have been analyzed in recent years in the Scopus international database. On the basis of the above, the necessary further steps and approaches in the policy of the journal are outlined for the growth of its scientometric indicators in order to achieve its high level.